Diversity and Seasonal Distribution of Plankton in Khaste Lake, Lekhnath, Kaski, Nepal - Bastakoti, Narayan Datta; Timilsina, Ganesh (Himalayan Biodiversity, 2020)
Planktons are the important components of aquatic ecosystem. In this study, we assessed the diversity and seasonal distribution of planktons in Khaste Lake, Lekhnath, Kaski. Samples were collected from three stations from April to September using plankton net of mesh size 60μm.The collection period included three different seasons: summer, early monsoon and late monsoon. Altogether 35 genera of plankton, 24 belonging to phytoplanktonic group and 11 to zooplankton, were recorded from April to September 2012. The recorded phytoplankton belonged to four classes namely chlorophyceae, bacillariophyceae, xanthophyceae, and cyanophyceae with fourteen, seven, two and one genera respectively, while zooplanktons belonged to three groups namely rotifera, cladocera and copepoda with three, six and two genera respectively. The dominant class in phytoplankton was chlorophyceae with fourteen genera and in zooplankton was cladocera with six genera. Eleven genera of phytoplankton and five genera of zooplankton were recorded throughout the three seasons of the study period. The rich in diversity of phytoplankton shows high level of nutrient status and the lake changing into Eutrophication Lake resulting from the surface run-off water with fertilizers from agricultural lands and sewage from densely populated area of the surrounding.